A Study on the impact of the merit/demerit system on the clinical performance of fourth year medical students at the De La Salle University Medical Center - Pacifico Jaime L.; Melflor A. Atienza, MD MHPEd (2008)
The basic goal of all medical schools is to produce competent health professionals. Terminal competencies for fourth year medical students include obtaining an adequate history, thorough physical examination, diagnosing, planning management and performing simple treatment procedures. Evaluation of these competencies especially the non-cognitive aspect is difficult and hardly given emphasis during the clinical rotation of students. The merit/demerit system is an evaluation tool that has been in use in many medical schools in the Philippines to discourage delinquency among students and reinforce professional attributes expected of future physicians. However, it has been criticized for being prone to abuse and to be of minimal effectiveness. This study determined the current perceptions of the clinical clerks towards the merit/demerit system; determined the association between merit/demerit, perceptions and clerks' characteristics and their rotation performance; and lastly to identify the strengths and weaknesses of merit/demerit system. Population of the study referred to all clerks at the De La Salle University College of Medicine. Out of 93 fourth year medical students enrolled for the school year 2007-2008, 86 participated in the study with a response rate of 92.5%. Fifty three are females and 33 are males, the age ranged from 21 to 31 with a mean age of 24.76 years. Majority of the students agreed the demerits and merits were justified. Ninety percent of the respondents concurred that even stiff sanctions are appropriate when the delinquency could compromise patient care. Consistency of implementation of the merit/demerit system received a very poor rating from the respondents. There was no correlation between the rotation grade and the perceptions of the merit/demerit system, clerks' characteristics, premedical school and residence during clerkship. Some of the strengths include motivating the respondents to do their clinical histories and reporting for duty on time. The system also helped developed among majority of the students values that are expected of a health professional such as responsibility, discipline and honesty among others. Weaknesses of the system include inconsistency in implementation, apparent abuse by the consultants and residents and underutilization and lack of guidelines regarding merits. The merit/demerit system remains a relevant tool in clerkship but needs constant evaluation and improvement so it continues to be an effective assessment strategy in clerkship.
Thesis (Master in Health Professions Education)--University of the Philippines Manila
Panel Members: Melflor A. Atienza MD MHPEd, Chair/Adviser; Erly A. Sana PhD, Reader/Critic; Nemuel S. Fajutagana MD MHPEd, Member; Nomar M. Alviar MD MHPEd, Member; Melchor Frias MD MDCE.
Keywords: De La Salle University Medical Center; Merit (Ethics)